2014
DOI: 10.1002/ejhf.70
|View full text |Cite
|
Sign up to set email alerts
|

Combined aerobic/inspiratory muscle training vs. aerobic training in patients with chronic heart failure

Abstract: Aims Vent‐HeFT is a multicentre randomized trial designed to investigate the potential additive benefits of inspiratory muscle training (IMT) on aerobic training (AT) in patients with chronic heart failure (CHF). Methods and results Forty‐three CHF patients with a mean age of 58 ± 12 years, peak oxygen consumption (peak VO2) 17.9 ± 5 mL/kg/min, and LVEF 29.5 ± 5% were randomized to an AT/IMT group (n = 21) or to an AT/SHAM group (n = 22) in a 12‐week exercise programme. AT involved 45 min of ergometer training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
134
1
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(160 citation statements)
references
References 39 publications
6
134
1
8
Order By: Relevance
“…These results are broadly consistent with those of Laoutaris et al, who concluded that improvements in dyspnea and exercise tolerance after and consistent with those of previous studies, which have shown a similar attenuation of remodeling mainly attributed to a decrease in peripheral vascular resistance following aerobic exercise [31]. The results of this study are in agreement with those of previous studies that compared inspiratory muscle training with other modes of training These studies reported that the addition of inspiratory muscle training to aerobic training [13,28] or combined aerobic and resistance training [32] resulted in significant improvements in respiratory muscle strength, functional capacity, and cardiorespiratory responses to exercise in patients with chronic heart failure and inspiratory muscle weakness. [13,28,32] However, our findings are contradicted by those of Weiner et al [33], who failed to achieve a significant improvement in peak exercise oxygen consumption following 3 months of specific inspiratory muscle training, and Adamop-oulos et al, who reported that the addition of inspiratory muscle training to aerobic training gained an additional improvement in respiratory muscle function without significant changes in cardiopulmonary exercise testing [13].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are broadly consistent with those of Laoutaris et al, who concluded that improvements in dyspnea and exercise tolerance after and consistent with those of previous studies, which have shown a similar attenuation of remodeling mainly attributed to a decrease in peripheral vascular resistance following aerobic exercise [31]. The results of this study are in agreement with those of previous studies that compared inspiratory muscle training with other modes of training These studies reported that the addition of inspiratory muscle training to aerobic training [13,28] or combined aerobic and resistance training [32] resulted in significant improvements in respiratory muscle strength, functional capacity, and cardiorespiratory responses to exercise in patients with chronic heart failure and inspiratory muscle weakness. [13,28,32] However, our findings are contradicted by those of Weiner et al [33], who failed to achieve a significant improvement in peak exercise oxygen consumption following 3 months of specific inspiratory muscle training, and Adamop-oulos et al, who reported that the addition of inspiratory muscle training to aerobic training gained an additional improvement in respiratory muscle function without significant changes in cardiopulmonary exercise testing [13].…”
Section: Discussionsupporting
confidence: 93%
“…Maximum inspiratory pressure was assessed as a parameter of inspiratory muscle strength. Measurement was performed in a sitting position using Maximum Inspiratory Pressure Meter (care fusion UK 2321td) [13]. Each pa tient was asked to expire all of the air inside their lungs through the device, and then apply the mouthpiece while the nose was clipped, inspire as rapidly and deeply as possible, and hold their breath for at least 1.5 s so that the maximum pressure could be recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, it is possible that any training stimulus, regardless of specificity to respiratory muscles, may improve respiratory muscle strength and decrease related symptoms, such as dyspnea and exercise intolerance (38) . In a recent clinical trial, Adamapoulos et al (39) demonstrated important benefits with aerobic training exercise for respiratory muscle strength, supporting the results observed in this study.…”
Section: Discussionsupporting
confidence: 89%
“…When associated with aerobic exercise, high-intensity IMT presented significant improvement in MIP, quality of life, dyspnea, and C-reactive protein [16] .…”
Section: Introductionmentioning
confidence: 99%